“A Juridical Review Towards The Land Rights Ownership In Mixed Marriage” - Rahmia Rachman; Erlan Ardiansyah; Sahrul Sahrul (Jambura Law Review, 2021)
Mixed marriage causes a legal impact on Indonesian citizens marrying foreign citizens. They cannot have land rights since it is a part of joint property in marriage based on laws and regulations on land in Indonesia following the nationalism principles. The problem involved the guarantee of constitutional rights in land rights ownership is for the Indonesian citizens having a mixed marriage and the requirements for property/assets division agreement in a mixed marriage. This used normative legal research using the legislative approach and case approach. The legal materials consisted of primary legal materials, secondary legal materials, and tertiary legal materials that were then analyzed and concluded using the descriptive-qualitative method. The result was that the Indonesian citizens, having a mixed marriage with foreign citizens, had similar constitutional rights to other Indonesian citizens for land rights provided that the land was not included in joint property and proven by a marriage contract containing property/assets division. The marital property division agreement can be made at the time of or before the wedding, or during the marriage in the form of a Notarial Deed, and be legalized by a marriage registrar. For Moslems, it is registered in the Office of Religious Affairs, while for non-Moslems, it is registered in the Civil Registration Office. If the contract has been legalized, the content in the contract will bind the people who make it (husband and wife).